Media Fun Learning dalam Meningkatkan Soft Skills Anak Binaan di LPKA Kelas II Jakarta - Apriyanti Widiansyah; Rahmat Saputra; Husna Farhana; Anggi Larasati; Ayu Widya Fatmawati (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The partner in this program is the Jakarta Class IISpecial Child Development Institute (LPKA) located at JalanRaya Gandul, Cinere, South Jakarta, which is a place forchildren who are undergoing the justice process or serving acriminal term. Prisoners in the correctional process need to payattention to their rights, and need to be given legal protection.Article 85 of the SPPA Law states that Special ChildDevelopment Institutions (LPKA) are obliged to provideeducation, training, skills, guidance and fulfilment of otherrights, in accordance with the provisions of statutory regulations.LPKA students have the same information needs, because LPKAstudents or child prisoners are part of society who will return tosociety after serving their sentence. By providing the informationthey need, it will help them to socialize it back into society,becoming better citizens for themselves and the widercommunity. To overcome these problems, it is necessary to planfun learning media that can improve the soft skills of LPKAstudents, create a pleasant learning atmosphere, therebyincreasing the quality of students' knowledge and insight. Apartfrom that, it is necessary to carry out training in developingdiverse learning resources in the form of simple learning media,so that with this training, LPKA students can continue to innovatein creating a pleasant learning atmosphere.